Fabrication and investigation on field-dependent properties of natural rubber based magneto-rheological elastomer isolator - Wahab, N. A. A. (Institute of Physics Publishing, 2016)
This study presents a laminated magnetorheological elastomer (MRE) isolator which applies to vibration control in practice. The proposed isolator is fabricated with multilayer MRE sheets associated with the natural rubber (NR) as a matrix, and steel plates. The fabricated MRE isolator is then magnetically analysed to achieve high magnetic field intensity which can produce high damping force required for effective vibration control. Subsequently, the NR-based MRE specimen is tested to identify the field-dependent rheological properties such as storage modulus with 60 weight percentage of carbonyl iron particles. It is shown from this test that the MR effect of MRE specimen is quantified to reach up to 120 at 0.8 T. Following the design stage, the electromagnetic simulation using the finite element method magnetic (FEMM) software is carried out for analysing the magnetic flux distribution in the laminated MRE isolator. The laminated MRE isolator is then examined to a series of compression for static and dynamic test under various applied currents using the dynamic fatigue machine and biaxial dynamic testing machine. It is shown that the static compression force is increased by 14.5 under strong magnetic field compared to its off-state. Meanwhile, the dynamic compression test results show that the force increase of the laminated MRE isolator is up to 16 and 7 for low and high frequency respectively. From the results presented in this work, it is demonstrated that the full-scale concept of the MRE isolator can be one of the potential candidates for vibration control applications by tunability of the dynamic stiffness.